2020
DOI: 10.1002/fsn3.1867
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis: Does vitamin D play a promising role in sleep disorders?

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 55 publications
0
9
0
1
Order By: Relevance
“…This systematic review and meta-analysis investigated the effect of VDS on sleep quantity and quality, and sleep disorders. VDD is an emerging risk factor for suboptimal sleep and sleep disorders [ 12 , 15 , 43 ]. Such an association has been observed in several healthy and ill populations including factory workers, older community-dwelling men, hemodialysis patients, and pregnant women [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This systematic review and meta-analysis investigated the effect of VDS on sleep quantity and quality, and sleep disorders. VDD is an emerging risk factor for suboptimal sleep and sleep disorders [ 12 , 15 , 43 ]. Such an association has been observed in several healthy and ill populations including factory workers, older community-dwelling men, hemodialysis patients, and pregnant women [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also provided evidence that serum 25(OH)D below 20 ng/mL could significantly heighten the odds of unhealthy sleep [ 15 ]. Similarly, through a meta-analysis of observational studies conducted on 1864 subjects with sleep disorders and 1340 control participants, Yan et al [ 43 ] found that the average serum vitamin D concentration in the group with sleep disorders was 0.75 ng/mL lower than that in the control group [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…These factors increased in people with vitamin D deficiency. Therefore, they lead to sleep disorders such as OSAS (Obstructive Sleep Apnea Syndrom) (Yan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Significant evidence has indicated the association between various sleep behaviors and vitamin D metabolism ( 12 , 13 ). Several observational meta-analyses ( 14 , 15 ) showed obstructive sleep apnea (OSA) and sleep disorders were associated with lower 25(OH)D concentrations. There is evidence in showing there are vitamin D receptors in the brain involved in the sleep-wake cycle ( 16 ), providing a mechanistic explanation for how vitamin D deficiency can contribute to sleep disturbances.…”
Section: Introductionmentioning
confidence: 99%